2003
DOI: 10.1037/0894-4105.17.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Executive function, memory, and learning in Tourette's syndrome.

Abstract: Young people with Tourette's syndrome (TS) alone, TS plus attention-deficit/hyperactivity disorder (+ADHD), or TS plus obsessive-compulsive disorder (+OCD) were compared with a healthy control group on a set of measures of executive functioning, memory, and learning. The TS-alone group was impaired on one executive measure involving inhibition and strategy generation but did not differ significantly from the healthy control group on other measures. The TS+ADHD group showed impairment on several executive measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
139
3
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(162 citation statements)
references
References 44 publications
14
139
3
6
Order By: Relevance
“…Probably too many confounding factors are involved in the very complex Stroop task that a clear disorder-specific picture cannot be detected, or perhaps expected. In terms of CTD, our findings are in line with the general consensus that patients with CTD and even ADHD þ CTD did not differ in all Stroop parameters under investigation from controls (Channon et al 1992;Brand et al 2002;Channon et al 2003;Lavoie et al 2007;Marsh et al 2007;Roessner et al 2007a). The good Stroop task performance of the ADHD þ CTD group might be attributable to enhanced prefrontal capabilities in CTD (Rothenberger 1990;Serrien et al 2005;Plessen et al 2007) compensating the prefrontal deficits usually related to ADHD symptoms (Pliszka et al 2000;Albrecht et al 2005).…”
Section: Discussionsupporting
confidence: 79%
“…Probably too many confounding factors are involved in the very complex Stroop task that a clear disorder-specific picture cannot be detected, or perhaps expected. In terms of CTD, our findings are in line with the general consensus that patients with CTD and even ADHD þ CTD did not differ in all Stroop parameters under investigation from controls (Channon et al 1992;Brand et al 2002;Channon et al 2003;Lavoie et al 2007;Marsh et al 2007;Roessner et al 2007a). The good Stroop task performance of the ADHD þ CTD group might be attributable to enhanced prefrontal capabilities in CTD (Rothenberger 1990;Serrien et al 2005;Plessen et al 2007) compensating the prefrontal deficits usually related to ADHD symptoms (Pliszka et al 2000;Albrecht et al 2005).…”
Section: Discussionsupporting
confidence: 79%
“…27,28 Individuals with Tourette's disorder typically have normal intellectual functioning, although executive dysfunction, discrepancies between performance and verbal IQ, and a decrease in visual-motor skills have been associated with Tourette's disorder. 29 While the definitive pathophysiologic mechanism of Tourette's disorder has not been completely elicited, neuroimaging and neurophysiologic studies suggest the involvement of cortical-striatalthalamocortical pathways, especially a prefrontal dopaminergic abnormality. 30,31 While a variety of neurotransmitter systems, including dopaminergic, glutamatergic, GABAergic, serotonergic, cholinergic, noradrenergic, and opioid systems, are possibly involved in these corticostriatal-thalamocortical circuits, the dopaminergic system has especially gained attention due to therapeutic response of Tourette's disorder to antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…Learning implicit probabilistic rules in the weather prediction task, which depends at least in part on the caudate nucleus, is impaired (Keri, Szlobodnyik, Benedek, Janka, & Gadoros, 2002;Marsh et al, 2004). However, problems with procedural learning have not been found in rotary pursuit, mirror tracing, and serial reaction time tasks, all of which depend at least in part on procedural memory structures (Channon, Pratt, & Robertson, 2003;Marsh, Alexander, Packard, Zhu, & Peterson, 2005).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…In one, TS children were spared at picture naming (Scheurholz et al, 1996). In another, performance in a stem completion task was normal (Channon et al, 2003), suggesting that established lexical representations, and the priming of these representations, remains intact in TS. Finally, a third study found normal performance on the Wechsler Abbreviated Scale of Intelligence, which was used as an indirect measure of declarative memory function (Marsh et al, 2004).…”
mentioning
confidence: 98%
See 1 more Smart Citation